2002
DOI: 10.1034/j.1399-5618.4.s1.29.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune activation, steroid resistancy and bipolar disorder

Abstract: Kupka RW, Breunis MN, Knijff E, Ruwhof C, Nolen WA, Drexhage HA. Immune activation, steroid resistancy and bipolar disorder. 
 Bipolar Disord 2002: 4(Suppl. 1): 73–74. © Blackwell Munksgaard, 2002

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…40,46 No doubt, however, that the field has been pioneered by Drexhage et al 23 describing a raised number of pro-inflammatory (M1) monocytes in bipolar patients, by several technical means. 47, 48, 49 Thus, our study is the first independent confirmation of an M1 signature in monocytes from peripheral blood mononuclear cells of bipolar patients without medical comorbidities and strengthens the case for the identification of a subgroup of BD patients who may benefit by anti-inflammatory therapies. Altered monocyte cytokine profile can be the result of an immune or inflammatory process occurring in the central nervous system.…”
Section: Discussionsupporting
confidence: 73%
“…40,46 No doubt, however, that the field has been pioneered by Drexhage et al 23 describing a raised number of pro-inflammatory (M1) monocytes in bipolar patients, by several technical means. 47, 48, 49 Thus, our study is the first independent confirmation of an M1 signature in monocytes from peripheral blood mononuclear cells of bipolar patients without medical comorbidities and strengthens the case for the identification of a subgroup of BD patients who may benefit by anti-inflammatory therapies. Altered monocyte cytokine profile can be the result of an immune or inflammatory process occurring in the central nervous system.…”
Section: Discussionsupporting
confidence: 73%
“…A key feature of BD is shifts in mood states, and it has been suggested that immune system activation may vary across mood episodes of different polarity . During depressive episodes, an increase in proinflammatory cytokines, such as IL‐8, CRP and TNF‐α, was significant among patients with BD versus controls; whereas in mania, levels of IL‐6, IL‐8 and TNF‐α were found to be increased, with inconsistent results for IL‐4 . In another study, cytokine levels were compared in depressed, manic and euthymic patients with BD, finding an increase in IL‐2, IL‐4 and IL‐6 levels in mania and only increase of IL‐6 during depression, whereas euthymic patients showed an increase of IL‐4 .…”
Section: Resultsmentioning
confidence: 99%
“…IL-1b (OrtizDominguez et al 2007;Knijff et al 2007;Papiol et al 2004;Kupka et al 2002), IL-2 (Ortiz-Dominguez et al 2007;Breunis et al 2003;Liu et al 2004;Boufidou et al 2004), IL-6 (Ortiz-Dominguez et al 2007;Kim et al 2007;Padmos et al 2008;Kupka et al 2002), IL-8 (O'Brien et al 2006), IFNc (Liu et al 2004;Su et al 2002;Kim et al 2004;Boufidou et al 2004) as well as IL-2R (Breunis et al 2003;Tsai et al 2001;Tsai et al 1999;Maes et al 1995;Kupka et al 2002) and IL-6R (Ortiz-Dominguez et al 2007;Maes et al 1995;Rapaport et al 1999), and MDD e.g. IL-1b,, IL-2, IL-6, sIL-6R, IL-8,, TNFa, and interferon-c (IFNc) (Dowlati et al 2010;Miller et al 2009;Marques-Deak et al 2007;Schiepers et al 2005).…”
Section: Altered Cytokine Levelsmentioning
confidence: 99%